Energy minimization in cryogenic packed beds during purification of natural gas with high co2 content - Ali, A. (Wiley-VCH Verlag, 2014)
Minimization of energy consumption was explored for countercurrent switched cryogenic packed beds in which separation of CO2 and other components of natural gas can be achieved based on differences in freezing or desublimation points. Highly pure CO2 and methane were obtained after separation. An experimental setup for CO2 removal from natural gas was constructed and a detailed experimental study was conducted by changing different operating parameters. Compared to other cocurrent or jacket-cooled constant-temperature configurations, countercurrent switched beds provided optimal separation and energy efficiencies. The effects of important process parameters like initial temperature profiles of the cryogenic bed, feed composition, and feed flow rate on energy requirement, bed saturation, bed pressure, and cycling times were investigated. The energy requirement for cryogenic packed beds was compared with the conventional cryogenic distillation process. Â© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.